Influence of Recycled Fine Aggregates on the Structural Behavior of Reinforced Concrete Beams - Rodsin, Kittipoom; Ejaz, Ali; Shrestha, Kriti; Hussain, Qudeer; Parichatprecha, Rattapoohm (My University, 2025)
The research specifically focuses on the effects of recycled fine aggregates as partial replacements for natural aggregates, contributing to the growing body of knowledge on sustainable construction materials. This study contributes to the understanding of how recycled materials can be effectively utilized in concrete construction, promoting sustainability while maintaining structural integrity. The testing program includes 13 beams, all designed with a target compressive strength of 15 MPa, using seven different types of fine aggregates. All tested beams experienced mixed shear failure, starting with flexural cracks beneath the loading point and progressing to flexural-shear and diagonal shear cracks as the load increased. Failure was marked by significant diagonal cracks leading to brittle collapse and reduced beam capacity. Recycled aggregate beams exhibited a slight increase in flexural cracks, with critical shear cracks widening significantly when loads exceeded 50% of ultimate strength. The use of recycled brick aggregates, recycled concrete aggregates, fly ash, and sugarcane bagasse ash led to reduced shear strength and deflection capacity. Notably, recycled fine aggregate concrete beams with 10% cement clay interlocking bricks performed better than the control beam. The load-deflection response was similar across beams, indicating no impact on elastic stiffness.
Keywords: Beams; Concrete; Recycled fine aggregates; Shear failure; Sustainable materials